Comparative analysis of the SOL plasma in DEMO using EDGE2D/EIRENE and TECXY codes. (August 2017) - Rubino, G.; Ambrosino, R.; Calabrò, G.; Pericoli Ridolfini, V.; Viola, B.
Highlights: A benchmark of two plasma edge codes, TECXY and EDGE2D-EIRENE, is presented. A preliminary study of a DEMO scenario is performed assuming simplified hypotheses. The two codes predict different density, temperature and pressure target profiles. The predicted power density and total power reaching the divertor are similar. In well attached plasma conditions TECXY could be used for fast scoping studies. Abstract: In this contribution a benchmark of the 2D edge codes TECXY and EDGE2D-EIRENE is presented. A conventional DEMO scenario is considered by assuming a simplified geometry, with the target plates perpendicular to the separatrix, and a pure Deuterium plasma. Despite the different models adopted in the two codes, mainly related to the description of the neutral dynamics and to the different boundary conditions, the results show a good match both in terms of power load profiles on the outer target and predicted trends for global quantities. A scan in density and in diffusion coefficients is performed in order to identify the characteristic conditions and the different regimes of the SOL. Comparable values and similar dependency of the global quantities as a function of the power decay length is also observed.